One-pot synthesis of Bi-Ni nanowire and nanocable arrays by coelectrodeposition approach - Jia, Y.; Yang, D.; Luo, B.; Liu, Shaomin; Tade, Moses; Zhi, L. (SpringerOpen, 2012)
A novel and convenient one-pot electrodeposition approach has been developed for precisely controlled fabrication of large-scale Bi-Ni nanowire and nanocable arrays. Using porous anodic aluminum oxide as a shape-directing template, by simply changing the electrochemical deposition mode, desired Bi-Ni hybrid nanowires and Bi-Ni core-shell nanocables have been obtained in the CV and CC modes, respectively. The structure, morphology, and composition of the as-prepared samples were characterized using X-ray powder diffraction, transmission electron microscopy, elemental mapping, and energy-dispersive X-ray spectrometry.